ТАСВИРИЙ САНЪАТГА ОИД ЭНГ ҚАДИМГИ МАКОНЛАР (Scientific journal of the Fergana State University, 2023)
This article is about Zarautsai. Ancient focal point – Zarautsai, painted drawings on rocks, drawings in Zarautsai belong to the epoch of Poliolith, Mesoleit, Neolithic and Bronze Age. Figures and art are the spiritual wealth of the people, precious archaeological, historical monuments. This art is a rich heritage turned into value.